CONTINUING PROFESSIONAL EDUCATION: ANALYSIS WITH ACCOUNTING PROFESSIONALS FROM SERGIPE - Souza, Anny Karolinny Silva de; Mendonça, Gilvânia Francielle Silva; Rocha, Ronalty; Garcia, Adrianne (Revista UNEMAT de Contabilidade, 2023)
This study aimed to analyze the perception of the accounting professional about the importance of continuing education. For this, research was performed with a quantitative and qualitative approach, of simple descriptive character and application of descriptive statistical techniques. A questionnaire with open and closed questions by NBC PG 12 was used as a data collection instrument. Thus, a sample of 67 respondents was obtained, representing professionals registered with the Regional Accounting Council of the State of Sergipe (CRC/SE). The main results indicated that Sergipe accountants adopt mixed and face-to-face teaching modalities in universities, consulting companies, and courses offered by the regional Accounting Council, in the modalities of knowledge acquisition and teaching.Keywords: Continuing education. Accounting.  NBC PG 12.